Conductive resin composition and electromagnetic wave shielding material using same

By using phosphorus flame retardant in the conductive resin composition and controlling the content of coke powder and carbon fibers, the mesh structure is formed, and the problem of poor flame retardancy of the existing electromagnetic wave shielding materials is solved, and excellent electromagnetic wave shielding and flame retardancy are achieved.

CN119775657APending Publication Date: 2025-04-08MAZDA MOTOR CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411298953.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-09-18
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing electromagnetic wave shielding materials lack flame retardancy, especially when increasing the content of coke powder, the effect of the flame retardant is suppressed, resulting in poor flame retardancy.

Method used

By using foamed flame retardants, such as phosphorus flame retardants in the conductive resin composition, and controlling the content of coke powder and carbon fibers, a mesh structure is formed to improve conductivity and flame retardancy.

Benefits of technology

It achieves the improvement of electromagnetic wave shielding and flame retardancy while maintaining excellent mechanical characteristics and low cost, and meets the demand for high shielding rate and high flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047014170000031
    Figure BDA0005047014170000031
  • Figure BDA0005047014170000041
    Figure BDA0005047014170000041
  • Figure BDA0005047014170000042
    Figure BDA0005047014170000042
Patent Text Reader

Abstract

Provided are: a conductive resin composition which has both excellent electromagnetic wave shielding properties and excellent flame retardancy while maintaining excellent mechanical properties and low cost; and an electromagnetic wave shielding material which is produced using the conductive resin composition. The conductive resin composition contains a matrix resin, coke powder, carbon fibers, and a phosphorus-based flame retardant containing a (poly) phosphate salt. The coke powder has a volume average particle diameter of 1 [mu] m or more and 500 [mu] m or less. The content of the coke powder in the conductive resin composition is from 5% by mass to 17% by mass (inclusive). The aspect ratio of the carbon fibers is 3 to 1700 inclusive, and the content of the carbon fibers in the conductive resin composition is 0.5 mass% to 5 mass% inclusive. The content of the phosphorus-based flame retardant in the conductive resin composition is 10% by mass or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive resin composition and an electromagnetic wave shielding material made of the composition. Background Art

[0002] In recent years, in order to prevent the influence on the human body and prevent the malfunction of electronic equipment, etc., the conductive function is given to the covering materials used in automobile parts, electronic equipment, etc., and electromagnetic wave shielding is performed. Specifically, for example, by forming the covering material using a metal plate, etc., the covering material is used as the upper cover of the battery pack for electric vehicles, etc., to shield the electromagnetic waves emitted from the battery pack.

[0003] However, in order to achieve lightweighting of automobiles, electronic devices, etc., there is a demand to make the above-mentioned covering materials resin-based. For example, in the automotive field, various technologies that use electromagnetic waves to sense distance and speed, sense obstacles, etc. have been realized. In this technology, in order to accurately sense, it is necessary to shield unnecessary electromagnetic waves with high precision. As a covering material, it is also important to have excellent mechanical properties such as high rigidity and excellent cost-effectiveness.

[0004] Therefore, the inventors of the present application have proposed a conductive resin composition containing a matrix resin, coke powder and carbon fiber at a desired content ratio and an electromagnetic wave shielding material made of the composition (Patent Document 1). As for the conductive resin composition and the electromagnetic wave shielding material, by reducing the amount of carbon fiber added and increasing the amount of coke powder added, excellent electromagnetic wave shielding performance and excellent mechanical properties can be exhibited, while also achieving low cost.

[0005] Patent Document 1: Japanese Patent Publication No. 2021-161193 Summary of the invention

[0006] -Technical problem to be solved by the invention-

[0007] However, electromagnetic wave shielding materials are generally required to have fire resistance (flame retardancy). It should be noted that flame retardancy has not yet been considered in Patent Document 1. As a method of imparting flame retardancy to electromagnetic wave shielding materials, for example, it is possible to consider adding a flame retardant to a conductive resin composition as its material. However, when the content of coke powder increases, the effect and function of the flame retardant are suppressed, and sometimes the desired flame retardancy cannot be exhibited.

[0008] Therefore, the technical object of the present disclosure is to provide a conductive resin composition having excellent electromagnetic shielding properties and excellent flame retardancy while maintaining excellent mechanical properties and cost reduction, and an electromagnetic shielding material made of the composition.

[0009] -Technical solutions for solving technical problems-

[0010] The inventors of the present application have found that when a foaming flame retardant (e.g., a phosphorus flame retardant) is used, in a conductive resin composition containing a large amount (e.g., 20% by mass or more) of coke powder, the foaming of the flame retardant is suppressed, and the flame retardancy index is significantly poor. Based on this finding, the present disclosure suppresses the reduction in flame retardancy caused by the addition of coke powder (achieves an improvement in flame retardancy), and satisfies the required electromagnetic wave shielding without increasing the amount of coke powder and carbon fiber added.

[0011] The conductive resin composition disclosed herein contains a matrix resin, coke powder, carbon fiber, and a phosphorus-based flame retardant containing (poly)phosphate. The volume average particle size of the coke powder is 1 μm or more and 500 μm or less. The content of the coke powder in the conductive resin composition is 5% by mass or more and 17% by mass or less. The aspect ratio of the carbon fiber is 3 or more and 1700 or less. The content of the carbon fiber in the conductive resin composition is 0.5% by mass or more and 5% by mass or less. The content of the phosphorus-based flame retardant in the conductive resin composition is 10% by mass or more.

[0012] According to the described configuration, by making the content of the phosphorus flame retardant containing (poly) phosphate in the conductive resin composition to be 10% by mass or more, even if the content of coke powder in the conductive resin composition is 5% by mass or more and 17% by mass or less, the coke powder and carbon fiber as conductive filler (conductive material) will also form a cohesive structure in the matrix resin, and form a mesh. Therefore, a conductive path for current to pass through is formed in the matrix resin, and a seepage phenomenon in which conductivity increases sharply occurs. As a result, excellent electromagnetic wave shielding (electric field shielding) can be exerted. By making the content of coke powder to be 5% by mass or more and 17% by mass or less than 20% by mass, excellent flame retardancy can be exhibited without suppressing the foaming of the phosphorus flame retardant. In this way, by determining the respective content of coke powder and phosphorus flame retardant within the described range, the reduction of flame retardancy can be suppressed, and even if the content of carbon fiber is not increased, electromagnetic wave shielding can be improved, so low cost can be maintained. Moreover, by forming the described mesh, the excellent mechanical properties of the electromagnetic wave shielding material are maintained.

[0013] It should be noted that, in this specification, the so-called excellent electromagnetic wave shielding property refers to an electric field shielding effect (SE) of 45dB (shielding rate 99%) or more for electromagnetic waves with a frequency of 300kHz to 3MHz (more specifically, 1.7MHz) used in, for example, ship communications, medium wave broadcasting (AM broadcasting), ship and aircraft beacons, amateur radio, etc. Moreover, the measured value of the electric field shielding effect refers to a value measured according to the KEC method (a method for measuring electromagnetic wave shielding effect developed by the KEC Kansai Electronic Industry Promotion Center (KEC Kansai Electronic Industry Promotion Center)).

[0014] In this specification, excellent flame retardancy means that the limiting oxygen index (LOI) measured according to JIS K 7201 is 36% or more.

[0015] In one embodiment of the conductive resin composition, the phosphorus-based flame retardant is subjected to the following steps:

[0016] "(step)

[0017] The phosphorus-based flame retardant was mixed as a sample into a 1M nitric acid aqueous solution, and after stirring at room temperature 25° C. for 24 hours, the solution was passed through a membrane filter to prepare a measurement solution.

[0018] For the obtained measurement solution, ICP emission spectrometry was used to measure the content of iron and sodium elements. ”

[0019] When the content of iron in the phosphorus flame retardant is measured as F (ppm) and the content of sodium is measured as N (ppm), F and N satisfy 8.0×10 -4 ≤F / N≤20.0, F≤21.0. According to this configuration, the phosphorus-based flame retardant containing (poly)phosphate is determined.

[0020] The phosphorus-based flame retardant contains at least pyrophosphate, and the pyrophosphate is selected from the following general formula (1):

[0021] [Formula 1]

[0022]

[0023] (In the general formula (1), n ​​represents a number from 1 to 100, and X 1 represents ammonia or represents the following general formula (2):

[0024] [Formula 2]

[0025]

[0026] (In the general formula (2), Z 1 and Z 2may be the same or different and represents a group selected from the group consisting of -NR 5 R 6 group, hydroxyl group, mercapto group, linear or branched alkyl group having 1 to 10 carbon atoms, linear or branched alkoxy group having 1 to 10 carbon atoms, phenyl group, and vinyl group, R 5 and R 6 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 6 carbon atoms, or a hydroxymethyl group.) The triazine derivative represented by p is a number satisfying the relational expression 0 < p ≤ n + 2.)

[0027] or the following general formula (3):

[0028] [Formula 3]

[0029]

[0030] (In the general formula (3), r represents a number from 1 to 100, and Y 1 is a diamine, piperazine or diamine containing a piperazine ring represented by [R 1 R 2 N(CH2) m NR 3 R 4 , R 1 , R 2 , R 3 and R 4 are each a hydrogen atom, a linear or branched alkyl group having 1 to 5 carbon atoms, R 1 , R 2 , R 3 and R 4 may be the same or different, m is an integer from 1 to 10, and q is a number satisfying the relational expression 0 < q ≤ r + 2.)

[0031] selected from the group consisting of orthophosphate, pyrophosphate, and polyphosphate where n is 3 or more or r is 3 or more. According to this constitution, a phosphorus-based flame retardant containing (poly)phosphate and satisfying the relational expressions 8.0×10 -4 ≤ F / N ≤ 20.0 and F ≤ 21.0 is determined.

[0032] In one embodiment of the conductive resin composition, the content of the phosphorus-based flame retardant in the conductive resin composition is 30% by mass or less. According to this constitution, when the content of coke powder is 5% by mass or more and 17% by mass or less, flame retardancy can be obtained efficiently.

[0033] In one embodiment of the conductive resin composition, a flame retardant aid is further included. The content of the flame retardant aid in the conductive resin composition is 0.5 mass % or more and 5 mass % or less. According to these configurations, by adding the flame retardant aid, not only the flame retardancy is improved, but also the conductivity of the flame retardant aid itself helps to form a conductive path, thereby improving the electromagnetic wave shielding property.

[0034] In one embodiment of the conductive resin composition, the flame retardant auxiliary agent is zinc oxide. According to this configuration, the flame retardant auxiliary agent used in combination with the phosphorus-based flame retardant is determined.

[0035] In one embodiment of the conductive resin composition, a reinforcing filler is further contained. The content of the reinforcing filler in the conductive resin composition is 5% by mass or more and 40% by mass or less. According to these configurations, the addition of the reinforcing filler promotes the agglomeration of the coke powder, thereby improving the electromagnetic wave shielding property. It should be noted that, although the hardness of the carbon changes with the addition of the reinforcing filler, the effect on the flame retardancy is small.

[0036] In one embodiment of the conductive resin composition, the reinforcing filler is at least one selected from the group consisting of talc, calcium carbonate, glass fiber, aramid fiber and basalt fiber. According to this configuration, the reinforcing filler is determined.

[0037] The electromagnetic wave shielding material disclosed herein is made of the conductive resin composition, thereby being able to maintain excellent mechanical properties and low cost, and to achieve both excellent electromagnetic wave shielding properties and excellent flame retardancy.

[0038] - Effects of the Invention -

[0039] As described above, according to the present disclosure, it is possible to provide a conductive resin composition having both excellent electromagnetic shielding properties and excellent flame retardancy while maintaining excellent mechanical properties and cost reduction, and an electromagnetic shielding material made of the composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a graph showing the limiting oxygen index (LOI) of "addition system A" (comparative resin composition) containing coke powder and a phosphorus-based flame retardant and "addition system B" (conductive resin composition) containing coke powder, a phosphorus-based flame retardant, carbon fibers and glass fibers relative to the content of coke powder;

[0041] Figure 2It is a graph showing the electric field shielding effect of the "additive system B" and the "additive system C" (comparative resin composition) containing coke powder and carbon fiber (without flame retardant) at a frequency of 1.7 MHz relative to the content of coke powder;

[0042] Figure 3 It is a graph showing the limiting oxygen index (LOI) of each resin composition containing 0 mass% (no coke powder), 10 mass%, 20 mass% or 25 mass% of coke powder, a phosphorus-based flame retardant and carbon fiber relative to the content of the phosphorus-based flame retardant. DETAILED DESCRIPTION

[0043] The following description of the preferred embodiments of the present disclosure is merely illustrative in nature and is not intended to limit the scope of the present disclosure, its application objects, or its use.

[0044] <Conductive resin composition>

[0045] The conductive resin composition of this embodiment contains a base resin, coke powder, carbon fiber, and a phosphorus-based flame retardant. In other words, a conductive filler and a flame retardant are added to the base resin. The conductive resin composition can be used as a molding material for an electromagnetic wave shielding material described later.

[0046] (Base resin)

[0047] The matrix resin is a thermoplastic resin and / or a thermosetting resin. Examples of thermoplastic resins include polystyrene, vinyl acetate, polyester, polyethylene, polypropylene, polyamide, rubber, acrylic and other resins. Examples of thermosetting resins include unsaturated polyesters, phenols, epoxies, polyurethanes, melamines, alkyds and other resins. The matrix resins can be used alone or in combination of two or more. From the perspective of ease of forming and reusability of electromagnetic wave shielding materials, the matrix resin is preferably a thermoplastic resin. From the perspective of cost and mechanical properties, polypropylene (PP) is more preferred among thermoplastic resins. The matrix resin can use a generally commercially available resin material.

[0048] From the viewpoint of improving moldability, the content of the matrix resin in the conductive resin composition is preferably 30% by mass or more, more preferably 35% by mass or more, and from the viewpoint of achieving both electromagnetic shielding properties and flame retardancy, the content of the matrix resin is preferably 50% by mass or less.

[0049] (coke powder)

[0050] Coke powder (hereinafter also referred to as "Coke") is a particle obtained by crushing a carbon material (coke) obtained by dry distillation of coal, coking (thermal polymerization) of petroleum or coal-based heavy oil. The coke powder is a relatively cheap material compared to carbon black and artificial graphite. In addition, coke powder has the same conductivity as carbon black or carbon fiber. Coke powder can use coke powder generally available on the market. Pitch coke powder can also be used as coke powder. Pitch coke powder is an easily graphitizable carbon material obtained by high-temperature calcination of soft pitch (SOP) to remove volatiles, and is expected to improve conductivity. The soft pitch is separated from coal tar, a by-product produced in the dry distillation (roasting) process of coal.

[0051] Examples of the shape of the coke powder include spherical, elliptical, flake, fibrous, and dendritic shapes. As the coke powder, coke powder of a single shape may be used, or coke powders of different shapes may be used in combination.

[0052] The volume average particle size (MV) of the coke powder is 1 μm or more and 500 μm or less. From the viewpoint of improving electromagnetic wave shielding, the volume average particle size of the coke powder is preferably 10 μm or more. From the viewpoint of improving formability, the volume average particle size of the coke powder is preferably 50 μm or less. It should be noted that in this specification, the volume average particle size refers to the volume weighted average diameter measured by laser diffraction and scattering method.

[0053] The content of coke powder in the conductive resin composition is 5% by mass or more and 17% by mass or less. From the viewpoint of improving electromagnetic wave shielding properties, the content of coke powder is 5% by mass or more, preferably 8% by mass or more, and more preferably 12% by mass or more. From the viewpoint of improving formability and reducing costs, and improving flame retardancy, the content of coke powder is 17% by mass or less, preferably 15% by mass or less.

[0054] The relationship between the content of coke powder and flame retardancy is as follows Figure 1 (See also Table 1) As shown, the limiting oxygen index (LOI) hardly changes in the range of 0 to 17 mass %, and decreases sharply when it exceeds 17 mass %. That is, the content of coke powder "17 mass %" can be said to be the change point of flame retardancy (effect). It should be noted that Figure 1 and the following Figure 2 The numbers recorded in correspond to the “numbers in the figure” in Table 1.

[0055] The relationship between the content of coke powder and electromagnetic wave shielding properties, such as Figure 2(See also Table 1) As shown, in order to ensure sufficient electric field shielding effect (for example, 45 dB or more) for electromagnetic waves with a frequency of 1.7 MHz, the content of coke powder needs to be "5% by mass or more". It should be noted that the electromagnetic wave shielding property of "addition system B" (conductive resin composition) is significantly higher than that of "addition system C" (comparative resin composition) which does not contain a flame retardant. That is, by further adding a flame retardant to the conductive filler in which coke powder and carbon fiber are combined, the electromagnetic wave shielding property can be improved, and the content of coke powder can be greatly reduced.

[0056] (Carbon Fiber)

[0057] Carbon fiber (hereinafter also referred to as "CF") can use commercially available carbon fibers such as polyacrylonitrile (PAN), pitch, cellulose, vapor-grown carbon fibers made of hydrocarbons, and graphite fibers. These carbon fibers can be used alone or in combination of two or more.

[0058] From the viewpoint of improving electromagnetic wave shielding, the average fiber length (weight average fiber length) of the carbon fiber is preferably 0.5 mm or more, more preferably 1 mm or more, further preferably 2 mm or more, and further preferably 3 mm or more. From the viewpoint of improving formability and mechanical properties, the average fiber length of the carbon fiber is preferably 25 mm or less, more preferably 10 mm or less. From the viewpoint of further improving electromagnetic wave shielding, among the carbon fibers, a long fiber specification carbon fiber with an average fiber length of 2 mm or more is preferred.

[0059] It should be noted that, in this specification, the average fiber length refers to the average value of the fiber lengths measured by extracting 100 or more fibers from a molded product. Examples of methods for extracting the fibers include an ashing method and the like.

[0060] From the viewpoint of improving electromagnetic wave shielding properties, the average fiber diameter of the carbon fibers is preferably 3 μm or more, more preferably 6 μm or more. From the viewpoint of improving formability and mechanical properties, the average fiber diameter of the carbon fibers is preferably 12 μm or less, more preferably 10 μm or less.

[0061] It should be noted that in this specification, the average fiber diameter refers to the average diameter obtained by dividing the sum of the single fiber diameters of the single fibers constituting the fiber bundle by the number of single fibers constituting the fiber bundle and taking the average value. The single fiber diameter refers to the average value of the maximum diameter and the minimum diameter of the cross section obtained when the single fiber is cut in a direction perpendicular to the fiber axis direction. It should be noted that the shape of the cross section of the fiber is not particularly limited and can be a perfect circle or an ellipse. The outer periphery of the cross section of the fiber can also be a wavy shape with bumps. The height of the bumps can be within about 10% of the single fiber diameter.

[0062] The aspect ratio of the carbon fiber is 3 or more and 1700 or less. From the viewpoint of improving electromagnetic wave shielding and mechanical properties, the aspect ratio of the carbon fiber is 3 or more, preferably 70 or more, more preferably 100 or more, further preferably 300 or more, and further preferably 500 or more. From the viewpoint of improving formability, the aspect ratio of the carbon fiber is 1700 or less, preferably 1000 or less, and more preferably 600 or less. It should be noted that in this specification, the so-called aspect ratio refers to the ratio of the length of the fiber in the length direction (fiber axis direction) to the length in the width direction orthogonal to the length direction. The aspect ratio refers to the value measured by laser diffraction and scattering method.

[0063] The content of the carbon fiber in the conductive resin composition is 0.5% by mass or more and 5% by mass or less. From the viewpoint of improving electromagnetic wave shielding properties, the content of the carbon fiber is 0.5% by mass or more, preferably 1% by mass or more, and more preferably 2% by mass or more. From the viewpoint of reducing costs, the content of the carbon fiber is 5% by mass or less, preferably 3% by mass or less.

[0064] From the viewpoint of improving electromagnetic wave shielding, the total content of coke powder and carbon fiber in the conductive resin composition is preferably 5.5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. From the viewpoint of improving formability and mechanical properties and reducing costs, the total content of coke powder and carbon fiber is preferably 22% by mass or less.

[0065] (Phosphorus flame retardant)

[0066] Phosphorus flame retardants are foaming flame retardants. Phosphorus flame retardants can use flame retardants that are generally available on the market. The inventors of the present application conducted in-depth research and found that by adding coke powder, the foaming ratio of phosphorus flame retardants is reduced (foaming is suppressed) and the limiting oxygen index (LOI) is greatly reduced. The inventors of the present application also found that by adding coke powder, the decomposition temperature of the matrix resin containing conductive fillers moves to the high temperature side, and the decomposition temperature increases significantly under an inert environment. Based on these findings, the mechanism of reduced flame retardancy caused by the addition of coke powder is considered to be as follows: (1) In a combustion environment, the decomposition temperature of the matrix resin containing conductive fillers increases significantly, so the phosphorus flame retardant begins to decompose (foam) first; (2) Since the foaming of the phosphorus flame retardant begins in the presence of resin around it, the foaming ratio is reduced due to the viscosity of the resin; (3) As a result, the thermal conductivity of the resin insulation layer becomes higher, the decomposition of the resin is promoted, and the flame retardancy is reduced.

[0067] Here, the phosphorus flame retardant is a phosphorus flame retardant containing (poly)phosphate. In this specification, (poly)phosphoric acid refers to any one of orthophosphoric acid, pyrophosphoric acid and polyphosphoric acid with a condensation degree of 3 or more, or a mixture thereof. (Poly)phosphate may contain two or more different degrees of polymerization or salt types.

[0068] As a phosphorus-based flame retardant containing (poly)phosphate, it is preferred that when the content of iron element in the phosphorus-based flame retardant measured in the following steps is defined as F (ppm) and the content of sodium element is defined as N (ppm), F and N satisfy 8.0×10 -4 Phosphorus flame retardant with ≤F / N≤20.0, F≤21.0.

[0069] (step)

[0070] An example of a measurement procedure of the content F (ppm) of the iron element and the content N (ppm) of the sodium element in the phosphorus-based flame retardant is as follows.

[0071] First, the phosphorus flame retardant is mixed as a sample into a 1M nitric acid aqueous solution, stirred at room temperature 25°C for 24 hours, and then passed through a membrane filter to prepare a measurement solution. For example, 50mL to 100mL of a 1M nitric acid aqueous solution can be added to 250mg to 500mg of a sample to prepare a measurement solution.

[0072] Next, for the obtained measurement solution, the content of iron and sodium elements is measured by ICP emission spectrometry. It should be noted that the calibration curve is made in the range of 0ppm to 0.5ppm or 0.5ppm to 10ppm for both Fe and Na. At this time, two calibration curves are used separately according to the Fe and Na detection intensities of the measurement solution. When the calibration curve range is exceeded, it can be diluted with 1M nitric acid aqueous solution to make the concentration enter the calibration curve range before measurement.

[0073] From the viewpoint of taking both electromagnetic wave shielding properties and flame retardancy into consideration, the upper limit of the content F of the iron element in the phosphorus flame retardant measured according to the above steps is preferably 21.0 ppm or less, more preferably 20.5 ppm or less, and further preferably 16.5 ppm or less. On the other hand, the lower limit of F is not particularly limited as long as it contains Fe, and from the viewpoint of improving flame retardancy, it may be, for example, 0.5 ppm or more, or 1.0 ppm or more.

[0074] From the viewpoint of achieving both electromagnetic wave shielding properties and flame retardancy, the upper limit of the content N of the sodium element in the phosphorus-based flame retardant measured according to the above procedure is preferably 5.1×10 3 ppm or less, more preferably 4.2×10 3 ppm or less, more preferably 3.0×10 3ppm or less. On the other hand, the lower limit of N is not particularly limited as long as it contains Na. For example, it can be 0.1 ppm or more, or 0.5 ppm or more.

[0075] From the viewpoint of achieving both electromagnetic wave shielding and flame retardancy, the upper limit of the content F (ppm) of iron element in the phosphorus-based flame retardant measured according to the above steps relative to the content N (ppm) of sodium element, that is, F / N, is preferably 20.0 or less, more preferably 19.0 or less, and further preferably 18.0 or less. On the other hand, from the viewpoint of improving flame retardancy, the lower limit of F / N is preferably 8.0×10 -4 or more, more preferably 9.0×10 -4 or more, and further preferably 1.0×10 -3 or more.

[0076] As the phosphorus-based flame retardant containing (poly)phosphate and satisfying the relational expressions of 8.0×10 -4 ≤F / N≤20.0 and F≤21.0, it is preferably to contain at least pyrophosphate, and the pyrophosphate is selected from the group of (poly)phosphates composed of orthophosphates, pyrophosphates represented by the following general formula (1) or the following general formula (3), and polyphosphates with n being 3 or more or r being 3 or more. The phosphorus-based flame retardants can be used alone or in combination of two or more.

[0077] [Formula 1]

[0078]

[0079] In the general formula (1), n represents a number from 1 to 100, and X 1 represents ammonia or a triazine derivative represented by the following general formula (2), and p is a number satisfying the relational expression of 0 < p ≤ n + 2.

[0080] [Formula 2]

[0081]

[0082] In the general formula (2), Z 1 and Z 2 can be the same or different and represent groups selected from the group consisting of -NR 5 R 6 groups, hydroxyl groups, mercapto groups, linear or branched alkyl groups having 1 to 10 carbon atoms, linear or branched alkoxy groups having 1 to 10 carbon atoms, phenyl groups, and vinyl groups, and R 5 and R 6 each independently represent a hydrogen atom, a linear or branched alkyl group having 1 to 6 carbon atoms, or a hydroxymethyl group.

[0083] [Formula 3]

[0084]

[0085] In the general formula (3), r represents a number from 1 to 100, and Y 1 is a diamine represented by [R 1 R 2 N(CH2) m NR 3 R 4 , piperazine, or a diamine containing a piperazine ring. R 1 , R 2 , R 3 and R 4 are each a hydrogen atom, a straight-chain or branched-chain alkyl group having 1 to 5 carbon atoms. R 1 , R 2 , R 3 and R 4 may be the same or different. m is an integer from 1 to 10, and q is a number satisfying the relation 0 < q ≤ r + 2.

[0086] In this specification, in the (poly)phosphate represented by the general formula (1), as a term representing a salt of (poly)phosphoric acid with a triazine derivative or ammonia, etc., triazine (poly)phosphate is used. In the (poly)phosphate represented by the general formula (3), as a term representing a salt of (poly)phosphoric acid with piperazine or a diamine containing a piperazine ring, etc., piperazine (poly)phosphate is used.

[0087] In the general formula (1), for example, when n is 1, it refers to orthophosphate; when n is 2, it refers to pyrophosphate; when n is 3, it refers to triphosphate.

[0088] In the general formula (3), for example, when r is 1, it refers to orthophosphate; when r is 2, it refers to pyrophosphate; when r is 3, it refers to triphosphate.

[0089] As the straight-chain or branched-chain alkyl group having 1 to 10 carbon atoms represented by Z 1 and Z 2 in the general formula (2), examples include: methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, tert-butyl, isobutyl, pentyl, isopentyl, tert-pentyl, hexyl, cyclohexyl, heptyl, isoheptyl, tert-heptyl, n-octyl, isooctyl, tert-octyl, 2-ethylhexyl, nonyl, decyl, etc. As the straight-chain or branched-chain alkoxy group having 1 to 10 carbon atoms, groups derived from these alkyl groups can be cited. As the -NR 1 and Z 2 that Z 5 R 6 in the group can take, the R 5 and R 6The linear or branched alkyl group having 1 to 6 carbon atoms represented by alkyl group may include the alkyl group having 1 to 6 carbon atoms among the alkyl groups exemplified above.

[0090] As X in the general formula (2) 1 Specific examples of the triazine derivatives represented by include melamine, acetoguanamine, benzoguanamine, acrylguanamine, 2,4-diamino-6-nonyl-1,3,5-triazine, 2,4-diamino-6-hydroxy-1,3,5-triazine, 2-amino-4,6-dihydroxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-propoxy-1,3,5-triazine, 2,4-diamino-6-isopropoxy-1,3,5-triazine, 2,4-diamino-6-mercapto-1,3,5-triazine, and 2-amino-4,6-dimercapto-1,3,5-triazine.

[0091] The phosphorus-based flame retardant preferably contains a pyrophosphate (pyrophosphate triazine, ammonium pyrophosphate) represented by the general formula (1). The phosphorus-based flame retardant preferably contains X in the general formula (1): 1 It is a pyrophosphate of melamine (melamine pyrophosphate). Thus, the flame retardancy can be stably improved.

[0092] In the general formula (3), Y 1 Examples of the diamines represented by R include: 1 R 2 N(CH2) m NR 3 R 4 , piperazine or diamine containing piperazine ring, etc. 1 ~R 4 The groups may be the same or different and represent a linear or branched alkyl group having 1 to 5 carbon atoms.

[0093] As the R 1 ~R 4 The linear or branched alkyl group having 1 to 5 carbon atoms represented by can be exemplified as the Z 1 and Z 2 Specific examples of the alkyl group represented by include alkyl groups having 1 to 5 carbon atoms.

[0094] Examples of the diamine containing a piperazine ring include compounds in which one or more of the 2, 3, 5, and 6 positions of piperazine are substituted with an alkyl group (preferably an alkyl group having 1 to 5 carbon atoms); and compounds in which the amino group at the 1 and / or 4 positions of piperazine is substituted with an alkyl group (preferably an alkyl group having 1 to 5 carbon atoms).

[0095] As Y in the general formula (3) 1Specific examples of the diamines represented include N,N,N',N'-tetramethyldiaminomethane, ethylenediamine, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, tetramethylenediamine, 1,2-propylenediamine, 1,3-propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, piperazine, trans-2,5-dimethylpiperazine, 1,4-bis(2-aminoethyl)piperazine, and 1,4-bis(3-aminopropyl)piperazine.

[0096] The phosphorus-based flame retardant preferably contains Y in the general formula (3): 1 It is a pyrophosphate of piperazine (piperazine pyrophosphate). This can stably improve the flame retardancy.

[0097] The phosphorus-based flame retardant may also contain both the (poly)phosphate represented by the general formula (1) and the (poly)phosphate represented by the general formula (3). 1 is a pyrophosphate of melamine (melamine pyrophosphate) and a piperazine (poly)phosphate represented by the general formula (3), and more preferably contains X in the general formula (1) 1 is pyrophosphate of melamine (melamine pyrophosphate) and Y in the general formula (3) 1 It is the pyrophosphate of piperazine (piperazine pyrophosphate). This can further improve the flame retardancy. It should be noted that the content ratio of the two can be appropriately selected.

[0098] The phosphorus-based flame retardant may contain one or both of orthophosphate and pyrophosphate in addition to pyrophosphate, thereby achieving a balance of various physical properties of the phosphorus-based flame retardant.

[0099] The content of the phosphorus flame retardant in the conductive resin composition is 10% by mass or more. From the viewpoint of improving flame retardancy, the content of the phosphorus flame retardant is 10% by mass or more, preferably 20% by mass or more. From the viewpoint of effectively improving flame retardancy, the content of the phosphorus flame retardant is preferably 30% by mass or less, more preferably 25% by mass or less.

[0100] Regarding the relationship between the content of coke powder and phosphorus flame retardant and flame retardancy, Figure 3As shown, in the range of 0 to 30 mass % (30 mass % or less) of the phosphorus flame retardant content and in the range of less than 20 mass % of the coke powder content, the limiting oxygen index (LOI) shows linearity and hardly decreases. On the other hand, in the range of 0 to 30 mass % (30 mass % or less) of the phosphorus flame retardant content and when the coke powder content is more than 20 mass %, the limiting oxygen index (LOI) does not show a linear relationship but decreases. In other words, in the range of more than 30 mass % of the phosphorus flame retardant content, the higher the coke powder content, the higher the flame retardancy. On the other hand, in the range of less than 30 mass % of the phosphorus flame retardant content, the flame retardancy is improved by making the coke powder content less than 20 mass %. In this way, since the coke powder content can be reduced in the range of less than 30 mass % of the phosphorus flame retardant content, the improvement of flame retardancy can be effectively achieved. That is, the content of the phosphorus-based flame retardant "30 mass %" can be said to be a change point at which the flame retardancy decreases due to the addition of coke powder.

[0101] Moreover, by Figure 1 to Figure 3 The results show that by using "5 mass % or more and 17 mass % or less" of coke powder and "10 mass % or more and 30 mass % or less" of phosphorus flame retardant in combination, a synergistic effect of both electromagnetic wave shielding (electric field shielding effect (SE) is, for example, 45 dB (shielding rate 99%) or more) and flame retardancy (limiting oxygen index (LOI) is, for example, 36% or more) can be obtained.

[0102] From the viewpoint of achieving both electromagnetic shielding properties and flame retardancy, the total content of coke powder and phosphorus flame retardant in the conductive resin composition is preferably 15 mass % or more, more preferably 30 mass % or more, further preferably 35 mass % or more, and preferably 47 mass % or less.

[0103] (Flame retardant additive)

[0104] The conductive resin composition involved in this embodiment may contain a flame retardant. The type of the flame retardant is not particularly limited. As the flame retardant used for the phosphorus flame retardant, metal compounds can be cited, such as zinc oxide. It should be noted that no matter which metal compound flame retardant is used, by adding the flame retardant, the conductivity of the flame retardant itself contributes to the formation of the conductive path, so that the electromagnetic wave shielding property can be improved.

[0105] From the viewpoint of achieving both electromagnetic wave shielding properties and flame retardancy, the content of the flame retardant auxiliary in the conductive resin composition is preferably 0.5% by mass or more and 5% by mass or less.

[0106] From the viewpoint of achieving both electromagnetic shielding properties and flame retardancy, the content of the flame retardant auxiliary relative to the matrix resin (100 mass %) (the content of the flame retardant auxiliary in the matrix resin) is preferably 3 mass % to 8 mass %.

[0107] (Reinforced filler)

[0108] The conductive resin composition of the present embodiment may also contain a reinforcing filler. By adding a reinforcing filler, the particle aggregation promotion effect brought by the mixture can be obtained. In other words, since the reinforcing filler contributes to the formation of the conductive path, the electromagnetic wave shielding property can be improved. By adding a reinforcing filler, the mechanical properties can also be improved.

[0109] Examples of reinforcing fillers include talc, calcium carbonate, glass fiber (hereinafter also referred to as "GF"), aramid fiber, basalt fiber, etc. The reinforcing fillers may be used alone or in combination of two or more. Reinforcing fillers generally available on the market may be used. Among the reinforcing fillers, glass fiber is preferred from the viewpoint of further improving mechanical properties and conductivity.

[0110] As the glass fiber, for example, commercially available glass fibers such as E glass and S glass can be used. These glass fibers may be used alone or in combination of two or more.

[0111] The average fiber length of the glass fiber is preferably 0.5 mm or more, more preferably 1 mm or more, further preferably 1.5 mm or more, and further preferably 2 mm or more. From the viewpoint of improving formability, the average fiber length of the glass fiber is preferably 10 mm or less, more preferably 5 mm or less. It should be noted that, from the viewpoint of further improving mechanical properties and conductivity, among the glass fibers, a glass fiber of a long fiber specification having an average fiber length of 1.5 mm or more is preferred.

[0112] From the viewpoint of improving mechanical properties, the average fiber diameter of the glass fiber is preferably 10 μm or more, more preferably 12 μm or more, and from the viewpoint of improving formability, the average fiber diameter is preferably 25 μm or less, more preferably 20 μm or less.

[0113] From the viewpoint of improving mechanical properties, the aspect ratio of the glass fiber is preferably 5 or more, more preferably 50 or more, and further preferably 100 or more. From the viewpoint of improving formability, the aspect ratio of the glass fiber is preferably 700 or less, more preferably 250 or less, and further preferably 150 or less.

[0114] From the viewpoint of improving mechanical properties and electromagnetic wave shielding properties, the content of reinforcing filler in the conductive resin composition is preferably 5% by mass or more, more preferably 15% by mass or more, and further preferably 20% by mass or more. From the viewpoint of improving formability, the content of reinforcing filler is preferably 25% by mass or less.

[0115] From the viewpoint of improving mechanical properties and electromagnetic wave shielding, the total content of coke powder, carbon fiber and glass fiber in the conductive resin composition is preferably 10.5% by mass or more, more preferably 30% by mass or more. From the viewpoint of improving formability and mechanical properties, and reducing costs, the total content of coke powder, carbon fiber and glass fiber is preferably 50% by mass or less.

[0116] (Other conductive materials)

[0117] It should be noted that the conductive resin composition may also contain other conductive materials (optional components) other than coke powder and carbon fiber within the scope of not reducing the effect of the present disclosure. Examples of other conductive materials include: carbon black; metal fibers; metal fillers such as copper powder, silver powder, nickel powder, silver-plated copper powder, gold-plated copper powder, silver-plated nickel powder, and gold-plated nickel powder; metal-coated resin fillers, etc. These other conductive materials may be used alone or in combination of two or more. Among other conductive materials, carbon black is preferred.

[0118] Examples of carbon black include acetylene black, gas black, oil black, naphthalene black, thermal black, furnace black, lamp black, channel black, roll black, pan black, and Ketjen black, based on their raw materials and production methods.

[0119] (Method for producing conductive resin composition)

[0120] Next, the method for producing the conductive resin composition is described. The pellets obtained by containing various components such as coke powder, phosphorus flame retardant, and flame retardant aids added as needed in the matrix resin are used as master batches. The master batches formed by mixing the various components in the desired addition ratio are put into a mixing extruder. The mixing extruder is, for example, a twin-screw extruder. The mixture put into the mixing extruder is melted and mixed, and the various components are evenly dispersed in the matrix resin, thereby preparing particles that become master batches. Next, the various components such as carbon fiber, glass fiber added as needed, and other conductive materials are mixed into the master batch in the desired addition ratio, and are evenly dispersed in the matrix resin, thereby obtaining a conductive resin composition.

[0121] <Electromagnetic wave shielding materials>

[0122] (Electromagnetic wave shielding materials)

[0123] The electromagnetic shielding material according to the present embodiment is formed from the conductive resin composition. Since the electromagnetic shielding material uses the conductive resin composition, it can maintain excellent mechanical properties and cost reduction, and can also have excellent electromagnetic shielding properties and excellent flame retardancy.

[0124] Electromagnetic wave shielding materials can be preferably used as covering materials for radar-related products, in addition to covering materials used around vehicles such as bumpers (front, left and right sides, and rear). It should be noted that the electromagnetic wave shielding material is not limited to vehicle parts, and can also be used for parts that need to shield electromagnetic waves, such as housings of general electronic equipment or robot bodies.

[0125] (Method for producing electromagnetic wave shielding material)

[0126] The manufacturing method of the electromagnetic wave shielding material is not particularly limited, and the electromagnetic wave shielding material having the desired shape can be obtained by the commonly used forming methods such as heating and pressurization. For example, in the case of injection molding, the molten and kneaded molten material (conductive resin composition) is injected into the mold and cooled, thereby manufacturing the electromagnetic wave shielding material. It should be noted that the molding method is not particularly limited, and in addition to the above-mentioned injection molding, it can also be, for example, extrusion molding, vacuum molding, compression molding, autoclave molding, resin transfer molding (RTM), etc.

[0127] <Effect>

[0128] According to the conductive resin composition involved in the present embodiment, since coke powder, carbon fiber and phosphorus flame retardant are used as conductive fillers, and the respective contents of coke powder and phosphorus flame retardant are determined, it is possible to suppress the reduction in flame retardancy caused by the addition of coke powder, and to obtain the particle coagulation promotion effect brought about by the addition of phosphorus flame retardant. As a result, an electromagnetic wave shielding material having both excellent electromagnetic wave shielding properties and excellent flame retardancy can be obtained. Moreover, by utilizing the particle coagulation promotion effect, a cohesive structure (net-like) of coke powder and carbon fiber is formed in the matrix resin, so that the mechanical properties of the electromagnetic wave shielding material are improved. The amount of coke powder and carbon fiber used is less due to the particle coagulation promotion effect, so the material cost is reduced, and a low-cost electromagnetic wave shielding material can be obtained.

[0129] (Example)

[0130] The present disclosure is described below based on embodiments. It should be noted that the present disclosure is not limited to the following embodiments, and the following embodiments can be modified and changed based on the gist of the present disclosure, and these modifications and changes are not excluded from the scope of the present disclosure.

[0131] <Manufacturing of conductive resin composition and electromagnetic wave shielding material>

[0132] As the matrix resin, polypropylene (PP) (model: J108M) manufactured by Prime Polymer Co., Ltd. was used. As coke powder (Coke), finely ground coke manufactured by Shin Chemical Co., Ltd. (volume average particle size: 24.1 μm) was used. As a phosphorus flame retardant, ADK STAB FP-2500S (main component: melamine pyrophosphate / piperazine pyrophosphate) manufactured by ADEKA Co., Ltd. was used. As a carbon fiber (CF) composite PP, PLASTRON (carbon fiber 40% added PP, average fiber length: about 0.9 mm to 4 mm, average fiber diameter: about 7 μm, aspect ratio: about 130 to 570) manufactured by Daicel Miraizu Co., Ltd. was used. As the glass fiber (GF) composite PP, HLG76B manufactured by GS Caltex (60% glass fiber added to PP, average fiber length: about 0.9 mm to 4 mm, average fiber diameter: about 17 μm, aspect ratio: about 53 to 230) was used. As the flame retardant auxiliary, zinc oxide was used.

[0133] The base resin, coke powder (Coke), phosphorus flame retardant, flame retardant additive and other additives added as needed are fed into a kneading extruder at the respective contents shown in Table 1, and these components are uniformly dispersed in the base resin to prepare pellets as master batches.

[0134] The masterbatch obtained above, carbon fiber (CF) composite PP, and additional components such as glass fiber (GF) composite PP added as needed were charged into an injection molding device at the contents shown in Table 1 (production of conductive resin composition).

[0135] Next, the conductive resin composition was injected into a mold (180mm×175mm×2.5mm) with a direct gate at one point to make a test resin plate (electromagnetic wave shielding material). An injection molding machine with a clamping force of 220t was used. The thickness of the test resin plate was 2.5mm. The molding conditions were a resin temperature of 220°C, a mold temperature of 40°C, a screw speed of 60rpm (the screw was a double-threaded screw), a back pressure of 3MPa, an injection speed of 100mm / s, and a holding pressure of 30MPa×15sec.

[0136] The mechanical properties, electromagnetic shielding properties (electric field shielding effect), and flame retardancy of the electromagnetic shielding material were evaluated by the following methods using the test resin plates obtained above.

[0137] <Evaluation of mechanical properties>

[0138] (Flexural strength and flexural modulus)

[0139] According to JIS K 7171, the obtained test resin plate was subjected to a three-point bending test to measure the bending strength and bending elastic modulus as bending properties. As a testing machine, a precision universal testing machine (Autograph AG-5kNX, manufactured by Shimadzu Corporation ((Strain) Shimadzu Corporation)) was used. It should be noted that during the measurement, the displacement speed was set to 2 mm / min and the measurement was carried out under an environment of 23° C. and 50 RH%.

[0140] <Evaluation of electromagnetic wave shielding properties (electric field shielding effect)>

[0141] The electric field shielding effect of the obtained test resin plate was evaluated by the KEC method using an electromagnetic wave shielding effect measuring device developed by KEC Kansai Electronic Industry Promotion Center (KEC Kansai Electronic Industry Promotion Center). An electromagnetic wave with a frequency of 1.7 MHz was used. The measurement was carried out in an atmosphere with a temperature of 25°C and a relative humidity of 30 to 50%.

[0142] <Evaluation of flame retardancy>

[0143] The flame retardancy of the test resin plate obtained above was evaluated by limiting oxygen index (LOI) according to JIS K 7201. It was also evaluated by cone calorimeter test according to JIS S1316.

[0144] [Table 1]

[0145]

[0146] - Industrial Applicability -

[0147] As described above, the conductive resin composition according to the present disclosure is useful as a molding material for an electromagnetic wave shielding material or the like.

Claims

1. A conductive resin composition comprising a base resin, coke powder, carbon fiber, and a phosphorus-based flame retardant containing (poly)phosphate, characterized in that: The volume average particle size of the coke powder is 1 μm or more and 500 μm or less. The content of the coke powder in the conductive resin composition is 5% by mass or more and 17% by mass or less. The aspect ratio of the carbon fiber is 3 or more and 1700 or less, The content of the carbon fiber in the conductive resin composition is 0.5 mass % or more and 5 mass % or less, The content of the phosphorus-based flame retardant in the conductive resin composition is 10% by mass or more.

2. The conductive resin composition according to claim 1, wherein: The content of the phosphorus-based flame retardant in the conductive resin composition is 30% by mass or less.

3. The conductive resin composition according to claim 1, wherein: When the content of iron in the phosphorus flame retardant measured in the following order is defined as F (ppm) and the content of sodium is defined as N (ppm), F and N satisfy 8.0×10 -4 ≤F / N≤20.0, F≤21.0, The steps are: The phosphorus-based flame retardant was mixed as a sample into a 1M nitric acid aqueous solution, and after stirring at room temperature 25° C. for 24 hours, the solution was passed through a membrane filter to prepare a measurement solution. The obtained measurement solution was analyzed by ICP emission spectrometry to measure the contents of iron and sodium.

4. The conductive resin composition according to claim 3, characterized in that: The phosphorus-based flame retardant contains at least pyrophosphate, which is selected from the group consisting of orthophosphates represented by the following general formula (1) or the following general formula (3), pyrophosphates, and polyphosphates wherein n is 3 or more or r is 3 or more. [Formula 1] In the general formula (1), n represents a number from 1 to 100, and X 1 represents ammonia or a triazine derivative represented by the following general formula (2), and p is a number that satisfies the relationship of 0 < p ≤ n + 2. [Formula 2] In the general formula (2), Z 1 and Z 2 Can be the same or different, indicating selection from -NR 5 R 6 a group selected from the group consisting of a hydroxyl group, a mercapto group, a linear or branched alkyl group having 1 to 10 carbon atoms, a linear or branched alkoxy group having 1 to 10 carbon atoms, a phenyl group, and a vinyl group, R 5 and R 6 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 6 carbon atoms, or a hydroxymethyl group, [Formula 3] In the general formula (3), r represents a number from 1 to 100, and Y 1 is a diamine, piperazine or diamine containing a piperazine ring represented by [R 1 R 2 N(CH2) m NR 3 R 4 , R 1 、R 2 、R 3 and R 4 are each a hydrogen atom, a straight-chain or branched-chain alkyl group having 1 to 5 carbon atoms, and R 1 、R 2 、R 3 and R 4 may be the same or different, m is an integer from 1 to 10, and q is a number satisfying the relationship 0 < q ≤ r + 2.

5. The conductive resin composition according to claim 1, wherein: The conductive resin composition further contains a flame retardant auxiliary agent, The content of the flame retardant auxiliary in the conductive resin composition is 0.5 mass % or more and 5 mass % or less.

6. The conductive resin composition according to claim 5, characterized in that: The flame retardant auxiliary agent is zinc oxide.

7. The conductive resin composition according to claim 1, wherein: The conductive resin composition further contains a reinforcing filler, The content of the reinforcing filler in the conductive resin composition is 5 mass % or more and 40 mass % or less.

8. The conductive resin composition according to claim 7, wherein: The reinforcing filler is at least one selected from the group consisting of talc, calcium carbonate, glass fiber, aramid fiber and basalt fiber.

9. An electromagnetic wave shielding material, characterized in that: Made from the conductive resin composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Conductive resin composition and electromagnetic wave-shielding material using the composition

    JP2021161193A